Stele–cortex interactions govern fine-root mechanics during short-term salinity stress in grapevine - Cesar Barrientos-Sanhueza; Flavia Dorochesi-Ollino; Andrés Zurita-Silva; Thorsten Knipfer; Italo F. Cuneo (Plant Stress)
The mechanical properties of roots are essential for plant anchorage, soil reinforcement, and overall root system function, particularly under stress conditions. Root tensile strength and elasticity play a key role in stabilizing plants and mitigating soil erosion, yet how these biomechanical properties respond to salinity stress remains poorly understood. Recent findings suggest that root mechanical behavior is not solely dictated by external dimensions but is significantly influenced by the interplay between internal tissue structures. This study examines how short-term (3 days) salinity stress alters the mechanical properties of grapevine fine roots by comparing traditional rootstocks with hyperarid-adapted genotypes from Chile’s Atacama Desert. By integrating uniaxial tensile strength testing with anatomical and physiological assessments, we demonstrate that salinity stress disrupts the load-bearing capacity of root tissues. In commercial rootstocks, extensive cortical lacunae formation increased stiffness while reducing resilience, limiting their ability to withstand mechanical stress. In contrast, hyperarid-adapted genotypes maintained greater elasticity and higher energy dissipation, mitigating structural failure. Our findings suggest that preserving stele–cortex interactions is a critical factor in root tensile strength under stress, reinforcing recent models of root reinforcement based on anatomical differentiation. These insights highlight the importance of root biomechanics in plant stress adaptation and suggest that integrating biomechanical assessments into plant physiology can improve breeding strategies for salt-tolerant crops with enhanced structural stability.